The Versatility of Tunnelling and Trenchless Methods for Sustainable Grid Construction - RETC2023 - P. Schmäh; M. Peters (Society for Mining, Metallurgy & Exploration, 2023)
The development of renewable energies and a sustainable power grid are the challenges for future energy supply. Underground cables will replace the vulnerable overhead lines, because of their safety benefits. Due to the public environmental awareness, smart tunnelling and trenchless solutions are required for inner-city and cross-country installations of underground cables, as well as for crossings and the landfall sections to connect offshore wind farms to the transmission grid. Methods from the tunnelling and pipeline industry provide a high flexibility in the planning of alignments, including versatile tunnel concepts and the installation of protective pipes with E-Power Pipe and Direct Pipe.